CX3CL1/CX3CR1 signal mediates M1-type microglia and accelerates high-altitude-induced forgetting - Wang, Xueting; Xie, Yuqi; Niu, Yun; Wan, Baolan; Lu, Yapeng; Luo, Qianqian; Zhu, Li (Frontiers in Cellular Neuroscience, 2023)
Introduction Hypoxia-induced neuronal damage is the primary cause of cognitive impairment induced by high-altitude exposure. Microglia play a crucial regulatory role in the central nervous system (CNS) homeostasis and synaptic plasticity. M1-type polarized microglia are suspected to be responsible for CNS injury under hypoxic conditions, but the exact molecular mechanism is still unelucidated. Methods CX3CR1 knock out and wide type mice were exposed to a simulated plateau at 7000 m for 48 h to construct the model of hypobaric hypoxia-induced memory impairment. The memory impairment of mice was assessed by Morris water maze. The dendritic spine density in the hippocampus was examined by Golgi staining. The synapses in the CA1 region and the number of neurons in the DG region were examined by immunofluorescence staining. The synapses in microglia activation and phagocytosis were examined by immunofluorescence. The levels of CX3CL1/CX3CR1 and their downstream proteins were detected. CX3CR1 knockout primary microglia were treated with CX3CL1 combined with 1% O2. The levels of proteins related to microglial polarization, the uptake of synaptosome and phagocytotic ability of microglia were detected. Results In this study, mice exposed to a simulated 7000 m altitude for 48 h developed significant amnesia for recent memories, but no significant change in their anxiety levels was observed. Hypobaric hypoxia exposure (7000 m altitude above sea level for 48 h) resulted in synapse loss in the CA1 region of the hippocampus, but no significant changes occurred in the total number of neurons. Meanwhile, microglia activation, increased phagocytosis of synapses by microglia, and CX3CL1/CX3CR1 signal activation were observed under hypobaric hypoxic exposure. Further, we found that after hypobaric hypoxia exposure, CX3CR1-deficient mice showed less amnesia, less synaptic loss in the CA1 region, and less increase in M1 microglia, compared to their wildtype siblings. CX3CR1-deficient microglia did not exhibit M1-type polarization in response to either hypoxia or CX3CL1 induction. Both hypoxia and CX3CL1 induced the phagocytosis of synapses by microglia through the upregulation of microglial phagocytosis. Discussion The current study demonstrates that CX3CL1/CX3CR1 signal mediates the M1-type polarization of microglia under high-altitude exposure and upregulates microglial phagocytosis, which increases the phagocytosis of synapses in the CA1 region of the hippocampus, causing synaptic loss and inducing forgetting.